2014
DOI: 10.1590/1982-021620143813
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades comunicativas de crianças prematuras e prematuras extremas

Abstract: Objetivo comparar o desempenho das habilidades comunicativas, de crianças nascidas prematuras, prematuras extremas e típicas de idade cronológica entre dois e três anos. Métodos participaram do estudo 72 crianças distribuídas em quatro grupos: 20 prematuros (GE-I), 16 prematuros extremos (GE-II) e 36 crianças com desenvolvimento típico (GC-I e GC-II), de idade cronológica entre dois a três anos. Houve pareamento quanto à idade cronológica e sexo. A avaliação constou da aplicação do Protocolo de Anamnese e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
9
0
4
Order By: Relevance
“…According to the neurological report and the image exams contained in the medical records, 33.3% of the children did not present alterations, 16.6% grade I periintraventricular hemorrhage (PIVH), 8.33% grade II and grade III PIVH, and 33.3% PIVH grade IV associated with periventricular leukomalacia (PVL). Regarding zygosity, 50% of the sample presented monozygotic and 50% dizygotic twinning (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the neurological report and the image exams contained in the medical records, 33.3% of the children did not present alterations, 16.6% grade I periintraventricular hemorrhage (PIVH), 8.33% grade II and grade III PIVH, and 33.3% PIVH grade IV associated with periventricular leukomalacia (PVL). Regarding zygosity, 50% of the sample presented monozygotic and 50% dizygotic twinning (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Language acquisition depends on neurobiological and social factors, which include the integrity of brain structures, proper cognitive function, social interaction, and the stimuli received in the child's environment. Deviations in any of these aspects may affect language development [16][17][18] , hence the importance of studies that evaluate language acquisition of twins in early childhood. Given the need to investigate language acquisition in cases of multiple pregnancies associated with prematurity, the aim of the present study was to describe the linguistic findings and investigate the presence of neurological changes in preterm twins.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the authors 13 pointed out that there were statistically significant differences in the communicative skills, while comparing the preterm group (preterm and extreme preterm) and the typical one, however, no statistically significant differences were seen, while comparing the preterm and the extreme preterm groups.…”
Section: -Communicative Behaviour Observationmentioning
confidence: 95%
“…In this group, neonates are classified as follows: Late Preterm (GA between 34 and 36 weeks), Moderately Preterm (GA between 30 and 33 weeks), and Extreme Preterm (GA <30 weeks). This biological risk factor can interfere with brain maturation, resulting in important functional impairments such as delays in motor, cognitive, personal-social and language development, which present high rates of occurrence (3) . Premature infants may also present delays in receptive and/or expressive language, with less communicative ability compared with that of infants born at term (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…This biological risk factor can interfere with brain maturation, resulting in important functional impairments such as delays in motor, cognitive, personal-social and language development, which present high rates of occurrence (3) . Premature infants may also present delays in receptive and/or expressive language, with less communicative ability compared with that of infants born at term (3,4) . A study (5) which investigated the effects of prematurity on language development suggested that preterm birth has a direct effect on infants' ability to produce the first language sounds and practice them in order to evolve into more complex constructions.…”
Section: Introductionmentioning
confidence: 99%